PREDICTING THE DETERMINANTS OF INTENTION TO REDUCE FOOD WASTE WITH FUZZY SET ANALYSIS - Gilang Kurniawan; Agustina Shinta Hartati Wahyuningtyas; Dwi Retno Andriani (Agricultural Socio-Economics Journal, 2022)
This study aims to predict the factors that drive the emergence of intentions to reduce food waste with a planned behavior theory approach. The study was carried out in Malang, East Java. The information was gathered through social media using a survey method with convenience sampling. The study employs fuzzy set qualitative comparative analysis (FsQCA).The research findings indicate four conditions in the subjective norm, perceived behavioral control, and feeling of guilt variables which are the core conditions needed to form an intention to reduce food waste. In addition, three of the four states were closely related to the general perception of caring and showed a tendency towards interpersonal and human-environmental awareness. Therefore, the recommended recommendation is a campaign movement that emphasizes community participation by adopting ideal food-management values that are simultaneous and supported by stimulation through public communication related to the minimization of food waste.